2021
DOI: 10.1177/10783903211017640
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Loneliness Among Youth During the Time of COVID-19: A Multinational Study

Abstract: BACKGROUND: Given the restrictions associated with COVID-19, feelings of loneliness among youth may increase. AIMS: The aims of the current study were to assess the prevalence of loneliness among young people at the time of COVID-19 and to identify whether selected variables related to the pandemic predicted the level of loneliness. METHOD: A cross-sectional study using WhatsApp and Facebook social media platforms was conducted to survey 1,057 young people aged 15 to 24 years from six Middle Eastern countries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 65 publications
(79 reference statements)
1
6
1
1
Order By: Relevance
“…Baseline loneliness scores from MINT participants indicated moderate loneliness both pre and post intervention [ 73 ]. Loneliness scores from MINT participants were similar to those measured among international samples of adolescents and young adults during the COVID-19 pandemic [ 74 , 75 , 76 , 77 , 78 ], indicating congruence between the sample in this study and other populations of adolescents. Given that the loneliness scores obtained in this study were measured during the COVID-19 pandemic, the scores may not be indicative of typical levels loneliness within this population.…”
Section: Discussionsupporting
confidence: 65%
“…Baseline loneliness scores from MINT participants indicated moderate loneliness both pre and post intervention [ 73 ]. Loneliness scores from MINT participants were similar to those measured among international samples of adolescents and young adults during the COVID-19 pandemic [ 74 , 75 , 76 , 77 , 78 ], indicating congruence between the sample in this study and other populations of adolescents. Given that the loneliness scores obtained in this study were measured during the COVID-19 pandemic, the scores may not be indicative of typical levels loneliness within this population.…”
Section: Discussionsupporting
confidence: 65%
“…Research showed that during the COVID‐19 pandemic, 48%, 44%, 34%, and 29.1% of adolescents experienced posttraumatic stress symptoms, sleep disorders, depression, and anxiety, respectively (L. Ma et al, 2021 ). At the same time, loneliness, low‐severe stress, perturbed about the pandemic, and attempted suicide were also found in adolescents with 59%, 26.9%, 24.5%, and 7,5%, respectively, during this pandemic (Al Omari et al, 2021 ; Gazmararian et al, 2021 ; T. Hou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, a study in the United Kingdom [4] reported a loneliness prevalence rate of 27% in 2020, while another study [5] found that 28.63% and 7.20% of the participants reported feeling lonely sometimes and often respectively, in 2020. A study based on six Middle Eastern countries conducted in 2021 reported that 40.6% of the respondents expressed a moderately high degree of loneliness [6]. Conversely, one study found no significant changes in loneliness during various phases of the pandemic [7].…”
Section: Introductionmentioning
confidence: 99%